- - دکتر فریده عصاره (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2000)
This article aims to study the subject of Third World countries research publications, during 1985-1989 in SCI, using citing-cited cItation analysis technique. The subject distribution of research publications of these countries will be studied in seven subject fields. The study found that, biomedical-biochemical field, ranked the first in the seven subject fields. The subject field of Third World Countries was also compared with the subject fields of world publications. The first top countries in the seven subject fields were identified and some s_ggestions were offered.